2013
DOI: 10.1111/jspn.12042
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a clinically useful measure of children's state anxiety before medical procedures

Abstract: Purpose Assessment of children’s anxiety in busy clinic settings is an important step in developing tailored interventions. This article describes the construct validation of the Children’s Anxiety Meter-State (CAM-S), a brief measure of state anxiety. Design and Methods Existing data were used to investigate the associations between child self-reports of anxiety, parent reports of child anxiety, and observed child distress during an intravenous procedure. Results Children’s (n = 421) CAM-S scores were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 56 publications
(60 reference statements)
1
45
0
Order By: Relevance
“…Young children are at greater risk for being more distressed with needle-related procedures (Ersig et al, 2013). Children who experience high levels of pain have higher levels of anxiety during invasive procedures (Noel, McMurtry, Chambers, & McGrath, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Young children are at greater risk for being more distressed with needle-related procedures (Ersig et al, 2013). Children who experience high levels of pain have higher levels of anxiety during invasive procedures (Noel, McMurtry, Chambers, & McGrath, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It validated at children aged 4–10 years during an intravenous procedure. CAM‐S scores were significantly associated with all parent measures and observed distress ratings (Ersig, Kleiber, McCarthy, & Hanrahan, ). Psychometric properties of CAM in Turkish population were conducted by Gerçeker, Binay, Bilsin, Kahraman, and Yılmaz (); they found that there was a significant negative correlation between the children's anxiety scores and their ages.…”
Section: Methodsmentioning
confidence: 99%
“…We used the CAM, a brief, validated self-report measure of anxiety for children 4–10 years of age, to measure state and trait anxiety (Ersig et al, 2013). Drawn to resemble a thermometer, the CAM has a bulb at the bottom with a horizontal line at each whole number.…”
Section: Methodsmentioning
confidence: 99%
“…; Ersig et al. ). Although distraction, analgesia and parental presence can be used to improve the experiences of children and young people having procedures within an acute environment (Kleiber and Harper ; Fanurik, Koh and Schmitz ; Piira et al.…”
mentioning
confidence: 97%
“…Children and young people have a moral right to have their voice and protests heard and respected and for these to inform judgements of their best interests and the actions of health professionals. Without robust evidence, debate and recognition that children are frequently held against their wishes in clinical practice for procedures which may not be urgent, children's rights will continue to be compromised.Children and young people find attendance and admission to hospital for clinical procedures frightening and anxiety provoking (Dahlquist et al 1986;Hart and Bossert 1994;Kain et al 2007;Jaaniste et al 2007;Ersig et al 2013). Although distraction, analgesia and parental presence can be used to improve the experiences of children and young people having procedures within an acute environment (Kleiber and Harper 1999;Fanurik, Koh and Schmitz 2000;Piira et al 2005), they are not infallible and there is little evidence-based guidance about how to act if a situation escalates and the first choice of intervention is ineffective.…”
mentioning
confidence: 99%